Short-Course of Methylprednisolone Improves Respiratory Functional Parameters After 120 Days in Hospitalized COVID-19 Patients (Metcovid Trial): A Randomized Clinical Trial - Barros, Camila Miriam Suemi Sato; Freire, Raissa Soares; Frota, Elisângela; Rezende Santos, Anna Gabriela; Farias, Maria Eduarda Leão; Rodrigues, Maria Gabriela Almeida; Silva, Bernardo Maia; Prado Jeronimo, Christiane Maria; Netto, Rebeca Linhares Abreu; Silva Borba, Mayla Gabriela; Baía-da-Silva, Djane; Brito-Sousa, José Diego; et al. (Frontiers in Medicine, 2021)
The use of corticosteroids may help control the cytokine storm occurring in acute respiratory failure due to the severe form of COVID-19. We evaluated the post-acute effect of corticosteroids used during the acute phase, such as impairment in pulmonary function parameters, on Day 120-follow-up, in participants who survived over 28 days. This is a Parallel, double-blind, randomized, placebo-controlled phase IIb clinical trial carried out between April 18th and October 9th, 2020, conducted in hospitalized patients with clinical-radiological suspicion of COVID-19, aged 18 years or older, with SpO2≤94% on room air or requiring supplementary oxygen or under invasive mechanical ventilation in a referral center in Manaus, Western Brazilian Amazon. Intravenous methylprednisolone (MP) (0.5 mg/kg) was given twice/daily for five days to these patients. Pulmonary function testing, maximal respiratory pressure testing, and other functional assessments were measured. Out of the total of surviving patients at day 28 (n=246) from the Metcovid study, a total of 118 underwent satisfactory pulmonary function testing (62 in the placebo arm and 56 in the MP arm), the supportive treatment was similar between placebo and MP groups (7[11%] vs 4[7%]; P=0.45). IL-6 levels were higher in the MP group (P<0.01). The need for ICU on admission (P=0.06), need for IMV (P=0.07), creatine kinase, (P=0.05) also tended to be higher in this group. In the univariate analysis, FEV1 and FVC were significantly higher in patients in the MP arm, being this last parameter also significantly higher in the multivariate analysis independently of IMV and IL-6 levels. In conclusion, the use of steroids for at least five days in severe COVID-19 was associated with a higher FVC, which suggests that hospitalized COVID-19 patients in the use of MP might benefit from its use in the long-term, with less pulmonary restrictive functions, attributed to fibrosis. Trial Registration: ClinicalTrials.gov Identifier: NCT04343729